2008
DOI: 10.1083/jcb.200712068
|View full text |Cite
|
Sign up to set email alerts
|

A cell-based reglucosylation assay demonstrates the role of GT1 in the quality control of a maturing glycoprotein

Abstract: The endoplasmic reticulum (ER) protein GT1 (UDP-glucose: glycoprotein glucosyltransferase) is the central enzyme that modifies N-linked carbohydrates based upon the properties of the polypeptide backbone of the maturing substrate. GT1 adds glucose residues to nonglucosylated proteins that fail the quality control test, supporting ER retention through persistent binding to the lectin chaperones calnexin and calreticulin. How GT1 functions in its native environment on a maturing substrate is poorly understood. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 65 publications
4
52
0
Order By: Relevance
“…Given the particular features of protein N -glycosylation in T. cruzi mentioned above, this is the first in vivo confirmation that UGGT recognizes preferentially advanced folding stages of an endogenous glycoprotein. This agrees with previous in vitro experiments or in vivo ones but using heterologously expressed glycoproteins [8,9,11,35]. In uggt −/− cells TcrCATL was unable to finish its folding process and was retained in the ER by BiP in a mostly extended conformation.…”
Section: Discussionsupporting
confidence: 91%
“…Given the particular features of protein N -glycosylation in T. cruzi mentioned above, this is the first in vivo confirmation that UGGT recognizes preferentially advanced folding stages of an endogenous glycoprotein. This agrees with previous in vitro experiments or in vivo ones but using heterologously expressed glycoproteins [8,9,11,35]. In uggt −/− cells TcrCATL was unable to finish its folding process and was retained in the ER by BiP in a mostly extended conformation.…”
Section: Discussionsupporting
confidence: 91%
“…We therefore hypothesize that the observed increase in association is due to local folding defects in domain D2 of the extracellular domain of gp130 DYY, evoked by the deletion mutation. It has been indeed shown that local folding defects in transmembrane proteins are recognized by the UDP-glucose:glycoprotein glucosyltransferase (UGGT) leading to reglucosylation of the glycan and, in consequence, a prolonged association of the misfolded protein with calnexin (Pearse et al, 2008;Taylor et al, 2004). Biophysical analysis of the recombinant gp130 domains D2-D3 containing a deletion mutation will reveal whether the mutations result in local structural instability.…”
Section: Discussionmentioning
confidence: 99%
“…The released substrate is now free to fold. If after a single round of lectin chaperone binding a nonnative conformation persists, the quality-control sensor UGT1 (UDP-glucose: glycoprotein glucosyltransferase 1) will transfer a glucose back onto the unglucosylated glycoprotein, regenerating monoglucosylated glycans (Labriola et al 1995;Sousa and Parodi 1995;Pearse et al 2008). The reglucosylated substrate can then reassociate with the lectin chaperones to continue with attempts to fold properly (Hammond et al 1994;Hebert et al 1995;Van Leeuwen and Kearse 1997;Wada et al 1997;Molinari et al 2005;Pearse et al 2008;.…”
Section: Carbohydrate-binding Chaperonesmentioning
confidence: 99%